The World of Dual-Brain - Zhang, Weizhi (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book leaves the template of the inertia of natural human society and traditional ideological thinking, to illustrate the mechanism of the generation of the Sociality Brain and to explore the construction path of the human-computer symbiosis order. At the same time, this book proposes concepts including 'wisdom sharing system', 'the Sociality Brain', 'dual-brain world', 'off-site economic civilization', 'basic contradictions in the intelligent world', and 'class analysis and division of the dual-brain world', etc. This is a philosophical thinking about the intelligent world beyond the categories of natural human society and biological brain.
The challenge of cognition -- The emergence of human-machine knowledge -- The dual-brain world -- Protection of sociality brain -- The inhuman community without humanity -- Class division -- Escape from kidnapping -- Human-machine symbiosis.
Keywords: Technology-Moral and ethical aspects; Science-Social aspects; Artificial intelligence; Ethics of Technology; Sociology of Science; Artificial Intelligence